THE NEED OF COMMUNICATION COMPETENCE IN CHURCH MINISTRY FOR PRIESTS AND MINISTERS - Sainyakit, Andreas (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2021)
Communication competence in Church ministry is essential for priests and ministers. The overarching argument is that, as a leader and public figures, priests and ministers should be communicative persons in dealing with people around them in different situation. Communication competence is based on the ability to perform an act of communication. It is also people’s ability to appropriately and effectively use communication to obtain a desired outcome or goal. Communication competence is needed also by priest and ministers to be able to recognize the given situation and how to respond it appropriately. However they live in the midst of people society with different cultures, languages, norms, rules. Therefore they are demanded to know more how to communicate and adjust themselves with such situations, and be able to find in them the life meaning. Such ability will help them to increase the quality of encounter or relationship which is applied by the way they speak and deal with others. Keywords: Need, Communication, Competence, Church, Ministry